Learning Innovation Together with Community: Inventing and Commercializing Slow-Release Organic Nano Fertilizer Pellets for Healthy and Sustainable Rice Agriculture - Karyasa, I Wayan; Widana, Gede Agus Beni; Astawa, I Putu Gede Banu; Mudianta, I Wayan (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
The village of Jagaraga, located in the Sawan district of Buleleng Regency, Bali Province, had significant potential in both culture and agriculture, particularly in rice farming. More than half of the village’s land area was rice fields, and over two-thirds of the villagers were rice farmers. However, ensuring healthy soils and crops through effective fertilizer solutions remained a major challenge. The aim of the community development initiative was to empower the village farmers to become innovative through collaborative learning and by inventing and commercializing a slow-release nano fertilizer. A participatory action and learning approach was used to engage the rice farming community. The Subak Babakan farmer organization and the local rice milling enterprise, PB Suwela Amertha, were involved in the empowerment activities, which included information sessions, training, technology application, guidance, evaluation, and sustainability planning. As a result, four formulas of slow-release organic nano fertilizers in pellet form were successfully developed. Additionally, a four-helix partnership involving academicians, the farmer community, enterprises, and the government was established to build a business platform for commercializing the innovation. Through this collaboration, academicians and community farmers successfully learned to address the primary challenges in rice agriculture innovatively while promoting sustainable practices to maintain the health of the land and the well-being of the villagers.